2013
DOI: 10.1039/c3cp51530c
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free gadolinium oxide for in vivo T1-weighted magnetic resonance imaging

Abstract: Gadolinium oxide (Gd2O3), which can be used as a T1-weighted magnetic resonance imaging (MRI) contrast agent, has attracted intense attention in recent years. In this paper, ligand-free monoclinic Gd2O3 nanocrystals of 7.1 nm in diameter are synthesized by a simple and green approach, namely microsecond laser ablation of a gadolinium (Gd) target in deionized water. These nanocrystals obtain high r1 relaxivity of 5.53 s(-1) mM(-1), and their low toxicity was demonstrated by the cell viability of S18 cells and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 36 publications
4
44
0
1
Order By: Relevance
“…For the same Ln, r 2 was found to increase with the magnetic field B 0 or with B 0 2 , , , . The dependence of r 2 on the particle size is more complex, as found experimentally, , and predicted by the OS theory , . For small particles, the Motional Averaging Regime (MAR) operates, and r 2 is proportional to ( µ eff ) 2 B 0 2 and inversely proportional to the radius of the NP.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…For the same Ln, r 2 was found to increase with the magnetic field B 0 or with B 0 2 , , , . The dependence of r 2 on the particle size is more complex, as found experimentally, , and predicted by the OS theory , . For small particles, the Motional Averaging Regime (MAR) operates, and r 2 is proportional to ( µ eff ) 2 B 0 2 and inversely proportional to the radius of the NP.…”
Section: Resultsmentioning
confidence: 56%
“…It is well‐known that the r 1 values for NPs increase as their size decreases, as the number of paramagnetic metal ions at the surface increases with their ( S/V ) ratio. Depending on the magnetic field, the r 1 values of Gd 2 O 3 NPs can go up to 12 (1.5 T) or 10 s –1 m m –1 (3 T) with optimal particle sizes of 1.6 and 3.8 nm, respectively , , , …”
Section: Resultsmentioning
confidence: 99%
“…124 Dendrimers can be used to either encapsulate or directly conjugate paramagnetic materials. [128][129][130][131][132][133] According to Ahmad et al,134 gadolinium oxide nanoparticles with dual imaging capacity can be used for MRI and CT. 126 In a recent communication, gadolinium (Gd) labeled nanoclusters functionalized with folic acid ligands was reported as a tumor-targeted T1 MRI contrast agent in vivo.…”
Section: Dendrimers For Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…21 We have previously reported that Ln carbonate NPs (turning into oxides upon calcination) can be readily prepared via controlled microwave-assisted seed growth. 23 Alternatively, a laser ablation method performed by focusing the laser beam onto a Gd target has been described, 24 resulting in spherical Gd 2 O 3 particles with an average diameter of 7 nm. Finally, the solvothermal method is dominating in the synthesis of upconversion NPs with highly controlled size and morphological uniformity.…”
Section: Introductionmentioning
confidence: 99%